2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319092
|View full text |Cite
|
Sign up to set email alerts
|

Differential pathlength factor estimation for brain-like tissue from a single-layer Monte Carlo model

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Thus, accurate quantification of NIRS signal is possible with information regarding nature of light transport through in-homogenous medium. Chatterjee et al ( 2015 ) analyzed a Monte-Carlo based computational model within a single layer of tissue like human brain. Their finding concluded that optical path changes by changing the source-detector separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, accurate quantification of NIRS signal is possible with information regarding nature of light transport through in-homogenous medium. Chatterjee et al ( 2015 ) analyzed a Monte-Carlo based computational model within a single layer of tissue like human brain. Their finding concluded that optical path changes by changing the source-detector separation.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the NIR light emitted by the source and detected by a near-by detector follows a banana-shaped path (Kamran et al, 2016 ). Thus, the actual path traveled by NIR light is much longer than the source-detector separation on the surface of the scalp (Delpy et al, 1988 ; Hiraoka et al, 1993 ; Chatterjee et al, 2015 ; Piao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…An erroneous DPF can yield an inaccurate estimation of hemodynamic responses (HRs) [33]. Some studies proposed a DPF estimation by an offline Monte-Carlo method [32,34,35], while others proposed approaches based on the analysis of a time-domain contrast function for compensation [36,37]. The Monte-Carlo method assumes that the DPF is identical for all channels, while the latter is only suitable for time-domain fNIRS.…”
Section: Introductionmentioning
confidence: 99%